Economics of Electric Vehicle Adoption: An Integrated Framework for Investigating the Antecedents of Perceived Value and Purchase Intent - Loudiyi, Hatim; Chetioui, Youssef; Lebdaoui, Hind (International Journal of Economics and Financial Issues, 2022)
Due to political instabilities, limited non-renewable resources and international conflicts, the energy industry has been subject to high volatilities in the last few years. This had negative effects on many developing economies, namely those importing most of their energy needs from other countries (i.e., Morocco). More recently, the high increases in energy prices have renewed interests and discussions related to the adoption of electric vehicles. The current study aims to examine Moroccan consumers’ perceptions and intentions to use electric cars (EV), an era marked by increasing cost of gasoline and other energy sources. Our study proposes an integrated model combining both contextual and technological factors that influence Moroccan consumer’s Perceived value and purchasing intention of electric vehicles. Data was collected using a self-administered questionnaire from 203 Moroccan respondents and the findings were analyzed using the partial least squares (PLS) technique. Our findings convey that Environmental responsibility and Policy incentives positively influence EV perceived value, while Environmental responsibility, Policy incentives, and perceived value positively influenced purchasing intention.